A Microstructure, Piezoelectric and Dielectric Properties of the PZT Ceramics Obtained by the Sol-Gel Method - Monika DUKAT; Aldona ZARYCKA (Archives of Acoustics)
A technological process to obtain ceramic materials by the sol-gel method replaces gradually conventional methods, based on a simple oxide synthesis as a result of high temperature sintering. The materials obtained by the sol-gel method are characterized by high density and better chemical purity. A powder with the Pb(Zr0:52Ti0:48)O3 chemical composition was obtained as a result of a synthesis by the sol-gel method and it was formed and sintered by a hot pressing method (HP). The specimens obtained were subjected to examinations of the dielectric properties, the tangent of dielectric loss angle, the piezoelectric properties and their micro-photographs were taken (SEM). A course of the technological process by the sol-gel method was described, the dielectric and piezoelectric parameters were determined and a microstructure and a domain structure were examined in the work.